Authority For Issuing Halal Certifikation In Indonesia : History, Philosofhy, And Institutions - Harahap, Syahrul Bakti; Perdana, Surya -; Wajdi, Farid - (Faculty of Law, Universitas Pekalongan, 2024)
The UUJPH's halal certificate laws have clarified matters for the protection of consumers, particularly Muslims. The state is adamant about shielding Muslim customers from goods that are neither halal nor certified halal. The Indonesian government has enacted Law Number 6 of 2023 addressing job development, which contains laws on the authority to issue halal certification and halal emblems in Indonesia, as well as Number 33 of 2014 concerning Halal Certification. These regulations aim to regulate halal certification in Indonesia. Based on a formal Fatwa granted by Indonesia, a halal certificate is an acknowledgement of a product's halalness issued by the Halal Product Guarantee Management Agency (BPJPH). The Ministry of Religion's Halal Fatwa Council and Ulema Council (MUI). This study employed normative juridical legal research, or qualitative research, by examining the legal norms and principles found in statutes. It was decided that the Indonesian Ulema Council (MUI) would be in charge of halal certification after literature research revealed that the government, specifically the Ministers of Religion, Health, and Home Affairs Number 42/Me.Kes/VIII/1985, originally had the authority to issue halal certificates.